2017
DOI: 10.4070/kcj.2016.0280
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Allocation and Specification of Cardiomyocytes during Zebrafish Embryogenesis

Abstract: Incomplete development and severe malformation of the heart result in miscarriage of embryos because of its malfunction as a pump for circulation. During cardiogenesis, development of the heart is precisely coordinated by the genetically-primed program that is revealed by the sequential expression of transcription factors. It is important to investigate how spatial allocation of the heart containing cardiomyocytes and other mesoderm-derived cells is determined. In addition, the molecular mechanism underlying c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…The difference between RV and LV in their developmental,4) biochemical5) or physical6) properties has been investigated by many, and some have reported that the RV shows an exaggerated response to various stimuli 7)8). Importantly, the RV undergoes greater workload during exercise6) while having lesser means of adaptation and is susceptible to damage compared to the LV, possibly leading to eccentric remodeling and fibrosis 9)…”
mentioning
confidence: 99%
“…The difference between RV and LV in their developmental,4) biochemical5) or physical6) properties has been investigated by many, and some have reported that the RV shows an exaggerated response to various stimuli 7)8). Importantly, the RV undergoes greater workload during exercise6) while having lesser means of adaptation and is susceptible to damage compared to the LV, possibly leading to eccentric remodeling and fibrosis 9)…”
mentioning
confidence: 99%